Staring at the Sun Tragedy, trauma, and ecological harmony - Gray, Tyson-Lord J. (2020)
Recently it has become increasingly evident that current theories of civilization are unsustainable. Within this essay I critique three alternative theories: bioregionalism, sustainable development, and The Universe Story. I argue that although these theories address ecological devastation, they fail to grapple with the legacy of white supremacy. Evoking Richard Wright's poem Between the World and Me, I argue that for minorities the landscape is often inscribed with trauma. Consequently, any theory of ecological harmony must take this into account. I refer to the task of contending with the legacy of slavery, colonization, and genocide as Staring at the Sun.
Keywords: Descartes; Richard Wright; Thomas Berry; bioregionalism; Ecology; Environmentalism; Sustainable Development